PARTICIPATION OF THREE CELL TYPES IN THE ANTI-SHEEP RED BLOOD CELL RESPONSE IN VITRO : SEPARATION OF ANTIGEN-REACTIVE CELLS FROM THE PRECURSORS OF ANTIBODY-FORMING CELLS - Tan, Teresita (The Rockefeller University Press, 1971)
Spleen cells of unprimed CBA mice were shown to produce anti-sheep red blood cell antibodies comparable in amount in vivo and in vitro. Under identical culture conditions spleen cells of C57BL mice did not respond. CBA spleen cells, passed through columns of cotton wool (CBAf), were equally inactive in vitro. However combined cultures containing both CBAf and C57BL cells yielded as many or more plaque-forming cells than the same number of unfractionated CBA spleen cells. Analysis of the contribution of each cell population to the synthesis of antibody in the combined cultures has disclosed the participation of three cell types. A thymus-dependent, radiosensitive cell was derived from the CBAf population, while the C57BL was the source of the precursor of the antibody-forming cell and of a radioresistant cell. The latter two were partially separated in a Staput apparatus.